2022
DOI: 10.1111/vco.12815
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of 101 dogs with oral melanoma treated with a weekly or biweekly 6 Gy × 6 radiotherapy protocol

Abstract: One radiotherapy (RT) protocol used for canine oral melanoma (OM) gives 36 Gy total, in six weekly or biweekly fractions (6 Gy × 6). This retrospective study characterizes oncologic outcomes for a relatively large group of dogs treated with this protocol and determines whether radiation dose intensity (weekly vs. biweekly) affected either progression‐free or overall survival (PFS and OS). Dogs were included if 6 Gy × 6 was used to treat grossly evident OM, or if RT was used postoperatively in the subclinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…This study revealed that advanced clinical stage was significantly associated with a shorter TTR and OS, as suggested by previous studies [ 3 , 4 ]. Median OS in our clinical setting was 144.5 days, which was shorter than that reported in a previous study (233 days) [ 3 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study revealed that advanced clinical stage was significantly associated with a shorter TTR and OS, as suggested by previous studies [ 3 , 4 ]. Median OS in our clinical setting was 144.5 days, which was shorter than that reported in a previous study (233 days) [ 3 ].…”
Section: Discussionsupporting
confidence: 87%
“…However, recurrence after radiation therapy is common. Several prognostic factors, such as tumor size, bone destruction, and clinical stage, to predict overall survival time have been identified in dogs with oral melanoma who have undergone radiation therapy [ 3 , 4 , 5 ]. Of those, the influence of tumor location and bone destruction on the efficiency of radiation therapy is a topic of debate, because there are few reports regarding time to recurrence after radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 4/6 of patients (66.6%) received prophylactic regional lymph node irradiation at the discretion of the attending radiation oncologist. In veterinary medicine, prophylactic nodal irradiation has been described for different tumor types, such as high-grade mast cell tumors in dogs ( 25 , 26 ), feline nasal lymphoma ( 27 ), and oral malignant melanoma ( 28 ). However, there is not a standard consensus for elective nodal irradiation in veterinary radiation oncology.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors that were proven to be prognostic in previous studies, including tumor information (tumor location [1], size [1], bone invasion status [28], and residue tumor before treatment [29]), clinical stage [1,29], histopathological features (mitotic count and lymphovascular invasion) [28,30], and treatments other than ACT were recorded. The response, adverse events of ACT, and peripheral blood neutrophil/lymphocyte ratio (NLR) before and after ACT, were also documented.…”
Section: Survival and Statistical Analysesmentioning
confidence: 99%